Edge superconductivity in multilayer WTe2Josephson junction - Sanvito, Stefano (My University, 2020)
WTe2, as a type-IIWeyl semimetal, has 2D Fermi arcs on the (001) surface in the bulk and 1D helical edge states in its monolayer. These features have recently attracted wide attention in condensed matter physics. However, in the intermediate regime between the bulk and monolayer, the edge states have not been resolved owing to its closed band gap which makes the bulk states dominant. Here, we report the signatures of the edge superconductivity by superconducting quantum interference measurements in multilayer WTe2Josephson junctions and we directly map the localized supercurrent. In thickWTe2(~ 60 nm), the supercurrent is uniformly distributed by bulk states with symmetric Josephson effect (|Ic+(B)|=|Ic-(B)| ). In thin WTe2 (10 nm), however, the supercurrent becomes confined to the edge and its width reaches up to 1.4 μm and exhibits non-symmetric behavior |Ic+(B)| = |Ic-c (B)|.The ability to tune the edge domination by changing thickness and the edge superconductivity establishes WTe2as a promising topological system with exotic quantum phases and a rich physics.
PUBLISHED
Keywords: exotic quantum phases; WTe2, as a type-IIWeyl semimetal; signatures; exotic quantum phases; WTe2, as a type-IIWeyl semimetal; signatures